2022
DOI: 10.5430/wjel.v12n6p352
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of the English Language Used in Social Media by Undergraduate English Majors in Jordan

Abstract: The study aims at investigating the frequency and willingness of undergraduate English majors to use English language in social media and informal context. It also aims at discovering frequently used expressions and exploring their functions. The study utilized a questionnaire developed by the researchers based on samples of students’ chats and posts collected from Facebook groups. The questionnaire was distributed to a sample of 100 students majoring English in Al-Hussein bin Talal University to elicit aspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Various social media platforms have been used as learning media. For example, Kreishan and Abbadi (2022) investigated the frequency of and willingness to use English in social media contexts among undergraduate English majors. Study results showed that social media had a significant effect in improving and developing English competence and skills in this technological era.…”
Section: Introductionmentioning
confidence: 99%
“…Various social media platforms have been used as learning media. For example, Kreishan and Abbadi (2022) investigated the frequency of and willingness to use English in social media contexts among undergraduate English majors. Study results showed that social media had a significant effect in improving and developing English competence and skills in this technological era.…”
Section: Introductionmentioning
confidence: 99%